Studi Perencanaan Infrastruktur Tempat Penampungan Sampah di Jalan KH. A. Rasyid Siddiq Kota Palembang - ., Sonia; ., Firdaus; Mulyati, Ely (Jurnal Sains dan Teknologi (JSIT), 2026)
Population growth and increased urban activity in Palembang City have resulted in an increase in waste volume, particularly in the KH. A. Rasyid Siddiq Road area, which has a high intensity of activity. The existing Temporary Storage Site (TPS) in the area does not meet technical standards, as indicated by its limited storage capacity, lack of waste sorting facilities, inadequate drainage system, and poor environmental aesthetics. This study aims to plan TPS infrastructure that meets waste generation needs, technical standards, and sustainable waste management principles. The research methods included literature studies, field observations, primary and secondary data collection, waste generation analysis, and technical design planning and budget plans (RAB). The results of the analysis show that the volume of waste at the research site reaches 6–8 tons per day with a projected increase to 125.49 m³/day by 2030. Based on the calculation results and land availability, the TPS is planned as a Type II TPS with an area of 192 m² and a storage capacity of 20–30 m³/day, equipped with sorting facilities, a composting area, a leachate drainage system, and a greening area based on the 3R concept. The estimated cost of cnstructing the TPS is IDR 277,060